The advances in acetylation modification in senescence and aging-related diseases - Xu, Maiqi; Wang, Wenbin; Lu, Saien; Xiong, Mengyao; Zhao, Tong; Yu, Yao; Song, Chunyu; Yang, Jinjing; Zhang, Naijin; Cao, Liu; Sun, Guozhe; Chen, Sichong; et al. (Frontiers in Physiology, 2025)
Aging is a process in which organisms or cells undergo a decline in their functions. Epigenetic modification changes have been recognized as a senescence hallmark in both natural aging and stimulation-induced senescence. An acetylation modification is a dynamic process, which plays a crucial role in the senescence process through DNA stability, metabolism, and signaling pathways. We summarized the role and regulatory pathways of acetylation modifications in senescence. Various cell fate-determining proteins regulate multiple cellular processes through acetylation modifications. These processes interact and coordinate with each other, forming an integrated regulatory network framework that collectively drives cellular senescence via multiple systemic mechanisms. Based on these findings, we proposed the “acetylation-network regulation-cellular senescence” model, to elaborate how acetylation contributes to senescence. We believe this insight could provide new directions and intervention strategies for senescence and aging-related diseases.